Atomic Nb Anchoring on Graphdiyne as a New Potential Electrocatalyst for Nitrogen Fixation: A Computational View. Issue 12 (19th September 2019) - Han, Xing‐Qi; Lang, Zhong‐Ling; Yan, Li‐Kai; Guan, Wei; Ci, Cheng‐Gang; Su, Zhong‐Min
Abstract: The exploration of effective active catalysts for the synthesis of ammonia NH3 is of vital importance to the development of the industrial dinitrogen‐fixation industry. Herein, a series of single transition metal atoms is screened anchoring on a monolayer graphdiyne (TM@GD, TM = Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ru, Rh, Pd, Ag, W, Ir, Pt, and Au) toward electrocatalytic N2 reduction reaction nitrogen reductive reaction (NRR) by density functional theory (DFT) calculations. Several TM@GD, including Ti@GD, V@GD, Nb@GD, Ru@GD, and W@GD, are computed to experience relatively lower free energy uphill for NRR than Ru(0001) surface. Specifically, the Nb@GD is demonstrated to be the most excellent for NRR with a limited potential of only 0.27 V, and also a high selectivity of 49.95% in spite of hydrogen evolution reaction (HER) competition simply estimated by Boltzmann distribution. Distal pathway is identified here without the formation of N2 N4 species, ensuring a highly oriented product of NH3 . Studies in this work would facilitate further experimental research in this field with a new idea and guidance to find out the active catalysts of high efficiency for NH3 synthesis at room temperature. Abstract : First principles calculations show that atomic Nb anchoring on a monolayer graphdiyne (Nb@GD) would act as a promising nitrogen reductive reaction (NRR) candidate with a low overpotential of 0.27 V and a selectivity of 49.95% in spite of the competition of hydrogen evolution reaction (HER) simply estimated by Boltzmann distribution, which exhibits good electrical conductivity and high thermal stability.